PENGARUH KONSENTRASI INHIBITOR UBI UNGU TERHADAP LAJU KOROSI BAJA KARBON A53 DENGAN MEDIA AIR LAUT - Ridho Unggul Nur Rahmadi; Imam Sholahuddin; Dwi Djumhariyanto (ROTOR, 2017)
Corrosion is a form of damage that occurs in metals. The main factor is the cause of the corrosion environment. A53 steel is a type of low carbon steel and a steel material types that are widely used for pipe applications. The use of a corrosion inhibitor is one way of preventing corrosion. Anthocyanin substances contained in purple yam can be made in a natural inhibitor, because the substance is an antioxidant anthocyanin which is an oxidation inhibitor. Variables used were varied concentration of 0 ppm, 2000 ppm, 4000 ppm and 6000 ppm. This study aims to determine the rate of corrosion, purpel sweet potato extract efficiencies and changes in microstructure. The method used in this study is experimental, inhibitor efficiency analysis, ANOVA test and analysis micro photo. The results showed that the material is corroded by pitting corrosion and uniform shape. Values on concentration lowest corrosion rate of 0.0044 mmpy 6000 ppm and 6000 ppm at the highest efficiency of 72.70%. Keywords: anthocyanin, steel A53, natural inhibitor, purple sweet potato.